Vegetation analysis of the subalpine beech forest on the upper forest line in the Julian Alps (NW Slovenia and NW Italy) and in the northern Dinaric Alps - Dakskobler Igor (Hacquetia, 2021)
Using hierarchical clustering with unweighted pair-group method with arithmetic mean (UPGMA) we arranged 603 phytosociological relevés of beech forests on the present upper forest line, mainly from the Julian Alps and the Trnovo Forest Plateau (we also included the relevés from the Karawanks and the Kamnik Alps), into 32 clusters. Based on their analysis and comparison with previously described similar (alti)montane-subalpine beech communities we classified most of the relevés into the association Polysticho lonchitis-Fagetum and its new subassociations ericetosum carneae, cardaminetosum trifoliae, luzuletosum niveae, luzuletosum luzuloidis, calamagrostietosum variae, allietosum victorialis, adoxetosum moschatellinae, stellarietosum nemorum and several new variants. The altitude of the studied stands is predominantly 1400 to 1550 m (the upper line is at 1660 m); they occur at all aspects, frequently on steep and very steep slopes, mainly on limestone and dolomite limestone, the predominant soil type is rendzina. These stands are species rich (on average 61 species per relevé, altogether more than 500 vascular plants) and have many species in common with the stands of associations Rhododendro hirsuti-Fagetum and Rhodothamno-Laricetum.